Exportation of trawl floats : a marketing appraisal of France, Portugal and Spain - Aðalsteinn Svan Hjelm; Bergsveinn Snorrason (2004)
Verkefnið er opið nemendum og starfsfólki Háskólans á Akureyri This thesis is a final thesis towards a B.Sc. diploma in the Faculty of Management at the University of Akureyri. It focuses on the possibilities of exporting Iceplast trawl floats to France, Portugal and Spain. To find this out, the research conducted here was split into two phases. The former sifted out the two less appealing markets, while identifying the market most likely to prove lucrative for Sæplast. The latter phase included further analysis of that particular market. The main observation question was as follows:  In which of these three markets, Frances, Portugal, or Spain should Sæplast concentrate on marketing its trawl float, and in what manner should this be conducted? Conclusions: France emerged as the most reliable country in light of economic strength, Spain filled the second place despite being the most attractive in the fishing industry factors but did not show the same economic health as France. Portugal is not a desirable market for marketing trawl floats as the fishing industry is dwarfed in comparison with that of Spain and France. At the same time Portugal’s economy is relatively underdeveloped, despite recent reforms. Sæplast should seek out and establish solid and trustworthy relationships with larger netting companies, establishing a small sales office in France to build up a close relationship with customers. This way Sæplast can use its sales office as a stepping stone for further growth in nearby foreign countries such as Spain. Also to be taken into consideration is the possibility of acquiring an existing business, thus moving Sæplasts production closer to its customers. Accultrating Sæplast’s brand names could substantially facilitate sales market penetration with trawl floats. Keywords: Plastic Industry, Trawl Floats, Exportation, Marketing, International Marketing.